The nitrogen nutrition of maize on dryland soils of the central Orange Free State - Schmidt, Gerhard Hermann Volkmar (Department of Molecular and Cell Biology, 2016)
1. Central Orange Free State soils vary considerably in the nitrogen supply to dryland maize. In some localities the soil supplies adequate amounts of nitrogen so that nitrogen fertilizer does not lead to any growth response. In other localities soils are poor in nitrogen and require nitrogen fertilizer for maximUIll grain yields. 2. In the localities investigated surface soils (0 - 1 ft.) did not differ appreciably in nitrogen status and the nitrogen supply to maize was influenced mainly by the nitrogen available in the respective subsoils (1-2 and 2-3ft.). 3. Differences in the nitrogen status between localities were evidently caused by appreciable differences in the mineral nitrogen cor;tents of the soils. The ability of the respective soils to liberate mineral nitrogen did not give any indication of the availability of nitrogen to maize in the field. These results may be partially explained by the semi-arid climatic conditions and relatively short periods of soil cultivation. 4. Differences in the nitrogen status of soils were strongly reflected in the nitrogen percentages of the plant material harvested at maturity. Nitrogen determinations in grain or stover seeD to be promising as a basis for the prediction of the, nitrogen requirel'lent of maize. 5. Weather conditions markedly influenced the response of maize to nitrogen fertilizer. In dry seasons response to nitrogen fertilizer may be low even on soils poor in available nitrogen. 6. When moist conditions allow a vigorous vegetative growth it is important that an adequate nitrogen status of the plants during the generative period be maintained by top-dressings. Limited amounts of nitrogen applied at planting time can lead to increased nitrogen requirement at an advanced stage of development. 7. In the Central Orange Free State the growth and reproduction of maize is limited mainly by moisture supply. A plant population of l5,OOO-plants per morgen is regarded as optimal for most seasons. A larger number of plants in- creases the nitrogen requirement of maize and the risk of failure in grain production. With a large number of plants per morgen generally more stover and less grain is produced, and more_nitrogen is retained in the stover than is the case with a smaller plant density. 8. Planting 15,000 plants per morgen led to only a slightly lower evapotranspiration as compared with 30,000 plants per morgen. 9. The drought resistance of maize can be increased slightly when the proposed number of plants is planted in wide (6 or 7 ft.) instead of in narrow (3 ft.) rows. Compared with 3 ft. rows, planting in 6 ft. rows resulted in only a slightly retarded evapotranspiration. O. Compared with early planting (October, November), delayed planting (December) increases the probability of a higher soil-moisture supply and may lead to increased grain yields. 1. Nitrogen fertilization does not seem to affect the drought resistance of maize or to decrease grain yields in dry seasons. 2. In hydroponic experiments, ammonium and nitrate applications led to a nearly equal growth of maize when higher NH₃⁻ tensions in the ammonium solutions were avoided. 3. In the physiology of maize the function of llitrates seems to be limited to a storage form of nitrogen. Hydroponic experiments did not indicate a significance of either NO₃⁻ or Cl⁻ as antagonists to polyvalent anions in this plant. Maize does not seem to be nitrophile or halophile.